Bedah Buku Biografi Abah Lukmanul Hakim bin Haji Musthofa Al-Banjari (Tokoh Islam Kharismatik Enok Dalam Abad ke-XX) - A. Muthalib; Khairuddin Khairuddin; Edi Ardian; Edi Susrianto; Nurbaidi Nurbaidi (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Talking about the history of a scholar (Islamic figure) in this country always attracts attention from various groups to be studied and studied further, in order to take lessons from the sides of his life to be emulated, imitated or emulated in our families and communities wherever they are, because Scholars are heirs of the Prophets. The history of Abah Lukman can be summarized as follows: Abah Lukmanul Hakim was a Ulama from the land of Banjar who had studied Islam in the holy city of Mecca and then after he returned to Indonesia then madam (wandered) to Indragiri Riau around 1914. Abah Lukmanul Hakim had studied with Mr. Sapat in Hidayat Village. At that time Abah lived in Tekulai Hilir. He was one of the special students when he studied at Hidayat, because in general he had studied the books studied in the village when he was in Mecca, but he wanted to take "blessings" from the descendants of Sheikh Muhammad Arsyad Al-Banjari who was famous in Tanah Banjar, a Ulama. Besar who authored the book "Sabilal Muhtadin", then after Tuan Guru Sapat died in 1939 Abah Lukman moved to Enok Dalam; Abah Lukmanul Hakim is someone who is consistent (consistent) in carrying out Islamic law; The legal basis for Abah Lukmanul Hakim being allowed to keep dogs for his community members at that time was to guard the coconut plantations, so that all the plants in their gardens were protected from pests such as pigs, monkeys and so on; Abah Lukmanul Hakim in the eyes of the people is a pious person. The heirs (sons and daughters) of Abah Lukmanul Hakim until this booklet was written, two people are still alive, namely: 1. Hj. Saibah and 2. Asy'ari, While in general there are still many grandchildren and they are scattered in several provinces in Indonesia such as: Jakarta, South Kalimantan, North Sumatra, Batam, Riau Islands, however, they mostly live in the Indragiri Hilir region of Riau, such as in Kec. Enok, Kec. Tempuling, Echo, Keteman (Scissors), and Kempas.